Safety and immunogenicity of the epicutaneous reactivation of pertussis toxin immunity in healthy adults: a phase I, randomized, double-blind, placebo-controlled trial. (June 2021) - Chatzis, O.; Blanchard-Rohner, G.; Mondoulet, L.; Pelletier, B.; De Gea-Hominal, A.; Roux, M.; Huttner, A.; Hervé, P.L.; Rohr, M.; Matthey, A.; Gutknecht, G.; Lemaître, B.; et al.
Abstract: Objectives: Protection induced by acellular vaccines can be short, requiring novel immunization strategies. Objectives of this study were to evaluate safety and capacity of a recombinant pertussis toxin (PTgen) -coated Viaskin® epicutaneous patch to recall memory responses in healthy adults. Methods: This double-blind, placebo-controlled randomized trial (Phase I) assessed the safety and immunogenicity of PTgen administered on days 0 and 14 to healthy adults using Viaskin® patches applied directly or after epidermal laser-based skin preparation. Patch administration was followed by Boostrix®dTpa on day 42. Antibodies were assessed at days 0, 14, 28, 42 and 70. Results: Among 102 volunteers enrolled, 80 received Viaskin-PT (Viaskin-PT 25 μg ( n  = 25), Viaskin-PT 50 μg ( n  = 25), laser + Viaskin-PT 25 μg ( n  = 5), laser + Viaskin-PT 50 μg ( n  = 25)), Viaskin-placebo ( n  = 10) or laser + Viaskin-placebo ( n  = 2). Incidence of adverse events was similar across groups (any local event: 21/25 (84.0%), 24/25 (96.0%), 4/5 (80.0%), 24/25 (96.0%), 8/10 (80.0%), 10/12 (83.0%), respectively). Direct application induced no detectable response. On day 42, PT-IgG geometric mean concentrations were significantly higher following laser + Viaskin-PT 25 μg and 50 μg (139.87 (95% CI 87.30–224.10) and 121.76 (95% CI 95.04–156.00), respectively), than laser + Viaskin-placebo (59.49, 95% CI 39.37–89.90). Seroresponse rates were higher following laser + Viaskin-PT 25 μg (4/5 (80.0%), 95% CI 28.4–99.5) and 50 μg (22/25 (88.0%), 95% CI 68.8–97.5) than laser + Viaskin-placebo (0/12 (0.0%), 95% CI 0.0–26.5). Conclusions: Viaskin-PT applied after laser-based epidermal skin preparation showed encouraging safety and immunogenicity results: anti-PT booster responses were not inferior to those elicited by Boostrix®dTpa. This study is registered at ClinicalTrials.gov (NCT 03035370) and was funded by DBV Technologies.